The new way things work - Macaulay, David; Ardley, Neil; Macaulay, David (Boston Houghton Mifflin Co, 1998)
Text and numerous detailed illustrations introduce and explain the scientific principles and workings of hundreds of machines. Includes new material about digital technology
Includes index
Rev. and updated ed. of: The way things work, 1988
2
Keywords: The World Around Us (Inventions )